The complement fixing properties and class distribution of rheumatoid factors (antiglobulins) in rheumatoid arthritis and other diseases. - March, R E (1982)
The MRSPAH (mixed reverse solid-phase passive antiglobulin haemadherence) test for antiglobulins (Agbs) of IgA, IgG and IgM classes has been quantified and also modified to measure their C3 fixing activity. An alternative ELISA technique is also described. Levels of all Agbs and their C3 fixing activity were significantly raised in established rheumatoid arthritis (RA) patients, early RA patients and established SLE patients. Ankylosing spondylitis (AS) patients had normal levels of Agbs and C3 fixation. Patients with infectious mononucleosis (IM) had high levels of all Agbs, but these did not fix complement. Thus, C3 fixing activity of Agbs is heterogeneous and raised levels are associated with the presence of joint disease. Isolated IgA, IgG and IgM fractions showed examples of Agbs which fixed C3. The proportion of C3 fixed per unit weight of Agbs was no greater in 'hidden' Agbs from serum and synovial fluids (SFs) than in untreated serum, and Agbs in SF do not fix more C3 than in serum. We conclude that the C3 fixing activity of Agbs is not directly related to affinity.